Follicle-Stimulating Hormone-Secreting Pituitary Adenoma Inducing Spontaneous Ovarian Hyperstimulation Syndrome, Treatment Using In Vitro Fertilization and Embryo Transfer: A Case Report - Du, Xiaofang; Zhang, Wen; Wang, Xingling; Yu, Xiaona; Li, Zhen; Guan, Yichun (Frontiers in Endocrinology, 2021)
Objective To describe the management of a patient with a pituitary adenoma secreting follicle-stimulating hormone (FSH) associated with spontaneous ovarian hyperstimulation syndrome (sOHSS) who was treated with in vitro fertilization and embryo transfer (IVF-ET). Methods We report a clinical case of a woman of reproductive age with menstrual irregularity, infertility and ovarian hyperstimulation due to recurrent pituitary adenoma secreting FSH, which persisted after transsphenoidal surgery.She underwent the diagnosis by magnetic resonance imaging (MRI) and laboratory tests,and finally she was treated with IVF-ET. Result(s) The patient was plagued by a recurrent pituitary adenoma for many years and tried various treatments. After complete transsphenoidal surgery, sOHSS decreased, as shown by a reduction in oestradiol levels and an improvement in the ultrasonography parameters; however, secondary amenorrhea occurred. Finally, pregnancy was achieved through IVF-ET and the symptoms of ovarian hyperstimulation were relieved. Conclusion(s) IVF-ET was found to be effective for the treatment of recurrent pituitary adenoma, thus representing a therapeutic option that should be taken into consideration in such cases.